2017
DOI: 10.1177/2192568217699191
|View full text |Cite
|
Sign up to set email alerts
|

Why Does C5 Palsy Occur After Prophylactic Bilateral C4-5 Foraminotomy in Open-Door Cervical Laminoplasty? A Risk Factor Analysis

Abstract: Study Design:Retrospective study.Objectives:To evaluate the efficacy of bilateral C4-5 foraminotomy in preventing occurrence of postoperative C5 palsy and to identify possible risk factors for its development.Methods:A total of 70 consecutive patients who underwent open-door laminoplasty with bilateral C4-5 foraminotomy were included. Clinical, radiographic, and operative data was reviewed. Development of postoperative C5 palsy was analyzed.Results:A total of 54 males and 16 females were reviewed. Mean age was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
0
17
2
Order By: Relevance
“…Sixteen studies met inclusion criteria for our systematic review. Three studies included patients receiving surgery through the anterior approach, 20,29,38 9 through a posterior approach, 15,30,31,33,39-43 3 through either the anterior or posterior approach analyzed together, 14,28,32 and 1 through the anterior or posterior approach analyzed separately, 44 (Table 1). Eighty-four different risk factors were analyzed, 27 of which were assessed in ≥2 studies and 57 in single studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sixteen studies met inclusion criteria for our systematic review. Three studies included patients receiving surgery through the anterior approach, 20,29,38 9 through a posterior approach, 15,30,31,33,39-43 3 through either the anterior or posterior approach analyzed together, 14,28,32 and 1 through the anterior or posterior approach analyzed separately, 44 (Table 1). Eighty-four different risk factors were analyzed, 27 of which were assessed in ≥2 studies and 57 in single studies.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have explored C5P mechanisms, and even more have examined its potential risk factors. 14-17,28-43 However, few of these factors have stood up to repeat scrutiny of being independent predictors for C5P occurrence. For example, although initially described in the setting of patients receiving surgery for ossification of the posterior longitudinal ligament (OPLL), 44 this disease has not been found to be causatively associated after further scrutiny.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study showed that prophylactic cervical foraminotomy reduced the incidence of C5 palsy compared with the control group (1.7% vs. 7.0%) through a 2-year prospective study, without adversely affecting cervical alignment, stability, hinge site, neurological recovery, and axial pain [16]. However, a recent retrospective study reported that prophylactic bilateral C4/5 foraminotomies did not eliminate the occurrence of C5 palsy [17]. We could not determine how many C5 palsy patients had received prophylactic cervical foraminotomy, but after the onset of C5 palsy, posterior cervical foraminotomy was performed in 7 cases (7.95%).…”
Section: Discussionmentioning
confidence: 99%
“…[11] Some studies had found that presence of intramedullary linear high intensity areas on both preoperative and postoperative T2-weighted MRIs were seen more at the level of paralysis but the association of these observations and the occurrence of C5 palsy were not consistent. [1,12-14]. …”
Section: Discussionmentioning
confidence: 99%